ANALISIS DI TAKE DOWN-NYA LAGU KEKE BUKAN BONEKA OLEH PIHAK YOUTUBE - Alexandra Nicole Karauwan; RR. Aline Gratika Nugrahani (Fakultas Hukum Universitas Trisakti, 2022)
Kekeyi is the singer and composer of the song Keke Not a Doll. The video for the song Keke Not a Doll was uploaded to YouTube about six days ago. YouTube later removed the video because to a copyright claim made by Rini Idol-Aku Not a Doll. The main issue is whether or not Kekeyi's song Keke Not a Doll violates the copyright for Kekeyi's song I'm Not a Doll and whether YouTube's action in removing the song is an attempt to protect that copyright of Novi Umar. It is legal research, use secondary evidence, descriptive and uses the deductive method to reach findings. According to the research, the song I'm Not a Doll by Novi Umar is copyleft protected. As a result, YouTube's removal of the song Keke Not a Doll by Kekeyi is an effort to uphold copyright, and Kekeyi took a significant portion of the song I'm Not a Doll. Not a Doll, which is a feature of the song I'm Not a Doll, in which the majority of the song's lyrics are derived, as well as copyright infringement, is governed by Article 44 of Law Number 28 of 2014 concerning Copyright.